Evaluation of topical 0.1% tazarotene cream in the treatment of palmoplantar psoriasis: An observer-blinded randomized controlled study - Bijal H Mehta; Sangeeta T Amladi (Wolters Kluwer Medknow Publications, 2011)
Background : Palmoplantar psoriasis is a frequently encountered variant of psoriasis. It is difficult to treat and even more difficult to maintain remission as it is exacerbated by friction and trauma of the patient's daily activities. Existing topical modalities of treatment are often inadequate and show unpredictable response. Aim : To study the efficacy and safety of a newer retinoid, tazarotene, as 0.1% cream in the treatment of palmoplantar psoriasis. Materials and Methods : Thirty adult patients with palmo-plantar psoriasis were randomized to therapy with once daily application of topical tazarotene cream (0.1%) or once daily application of clobetasol propionate cream (0.05%) for 12 weeks. The patients were assessed every 2 weeks for improvement in Erythema, Scaling, Fissures and Induration (ESFI) score and Physicians Global Assessment Scale. Results : At 12 weeks, the tazarotene group showed mean ESFI reduction to 1.12 (83.2%) from 6.65 at baseline. Complete clearance was noted in 52.9% of the patients. Clobetasol propionate group showed mean ESFI reduction to 0.62 (89.1%) from 5.69 at baseline, with complete clearance in 61.5% of the patients. Differences between the two groups were statistically insignificant. Side effects observed were initial irritation (41%) in the tazarotene group and hypopigmentation (53.8%) in the steroid-treated patients. Conclusion : Tazarotene is as effective as clobetasol propionate and provides a good alternative for the treatment of palmo-plantar psoriasis where hypopigmentation limits the use of clobetasol propionate cream.